Pembelajaran Tari Semarangan Di SLB Negeri Ungaran Kajian Penanaman Profil Pelajar Pancasila (Gotong Royong & Mandiri) - Widarwati, Widarwati (Fakultas Ilmu Pendidikan-Universitas Negeri Malang, 2024)
This research is motivated by the existence of an independent curriculum which has begun to be implemented in Indonesia in the 2022/2023 academic year, in the independent curriculum there are six character values that are expected to be achieved by students, namely faith, piety to God Almighty and noble character, global diversity, critical thinking, collaborative, independent, and creative. The implementation of the independent curriculum is of course carried out in all schools including Special Schools (SLB), therefore it is important for this research to be conducted to find out how the character values in the independent curriculum are applied in Special Schools (SLB). The purpose of this study is to analyze the inculcation of Pancasila student profiles in learning Semarangan dance, especially the values of mutual cooperation and independence. Data collection is done by interview, observation, and documentation. Testing the validity of the data using triangulation techniques with sources. The results of the study revealed that in learning the Semarangan Dance, Ungaran State SLB students, the teacher applied the planting of the Pancasila profile of mutual cooperation and independence with the result that the students could implement the values of mutual cooperation and independence. For students who are deaf and mentally impaired, they are able to carry out the values of mutual cooperation, such as taking dance properties to be used and preparing space for dance practice together. In addition, the value of independence is also instilled through learning the Semarangan dance when the teacher asks students to demonstrate the motions of the Semarangan dance individually.